THE EFFECT OF BRAND IMAGE ON CUSTOMER LOYALTY AT AROMA BAKERY & CAKE SHOP JL JENDERAL ABDUL HARIS NO 31 BC MEDAN JOHOR - Yuniarti Harahap (Movere Journal, 2022)
This study entitled "The Effect of Brand Image on Customer Loyalty in Aroma Bakery Cake & Shop Jl Jenderal Abdul Haris No 31 BC Medan Johor". The purpose of this study was to determine whether there is an influence of brand image on customer loyalty at Aroma Bakery Cake & Shop Jl Jenderal Abdul Haris No 31 BC Medan Johor. The data used in this study is primary data with the research instrument in the form of a questionnaire. The population used is 3400 customers/month. At Aroma Bakery Cake & Shop, using the slovin formula with the acquisition of a sample of 97 respondents. The method used in this research is descriptive quantitative method. The data analysis technique used simple linear regression analysis with the regression equation Y = 8,537 + 748X+ e. The results obtained in this study indicate a t-count value of 11.139 so it can be concluded that Brand Image has a positive and significant effect on Customer Loyalty at Aroma Bakery Cake & Shop Jl. Jenderal Abdul Haris No. 31 BC Medan Johor, while the coefficient of determination test value is 0.556 which indicates 56.6% of the brand image variables can explain its effect on customer loyalty and the remaining 43.4% is influenced by other factors outside of this research variable.